School Sanitation and Hygiene: Evaluating Waste Management in Birendranagar, Surkhet - Adhikari, Khagendra Parasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Many schools, particularly in low-income nations, lack adequate access to water facilities, sanitation, and hygiene education. Ensuring proper water, sanitation, and hygiene (WASH) infrastructure is essential for maintaining a healthy learning environment. Despite the recognized importance of WASH initiatives, significant gaps remain in their implementation, especially in schools where proper waste management and menstrual hygiene support are not always available. Objective: This study aims to assess the state of sanitation and hygiene management in secondary schools in Birendranagar, Surkhet, with a focus on waste management, hygiene practices, and infrastructure. Additionally, it seeks to evaluate the effectiveness of existing WASH initiatives in creating a healthier school environment. Methods: A descriptive research design was employed, using purposive sampling to collect data from 20 teachers and 107 students from two private and two government secondary schools in Ward No. 8, Birendranagar, Surkhet. Data collection focused on sanitation practices, hygiene education, waste management, and menstrual hygiene management. Findings: The study reveals that although sanitation education is included in the curriculum of most schools, health and hygiene programs are not consistently implemented. While handwashing stations and water supplies in restrooms are generally available, sustainable waste disposal and menstrual hygiene management remain significant challenges. Sanitary pad distribution is not always ensured, and although some schools provide separate facilities for boys and girls, menstrual waste disposal remains inadequate. Conclusion: The findings highlight an urgent need for improved WASH infrastructure and stronger hygiene education initiatives. Schools must prioritize consistent hygiene program implementation, ensure access to essential sanitary materials, and adopt sustainable waste management practices. Addressing these issues will contribute to better student health, well-being, and academic performance. Novelty: This study provides localized insights into WASH challenges in secondary schools in Birendranagar, Surkhet, highlighting the gaps in menstrual hygiene management and waste disposal. By emphasizing practical solutions for sustainable hygiene practices, the research contributes to a more comprehensive understanding of the barriers and opportunities in school sanitation management in low-income settings.